Pelatihan Penyusunan Soal High Order Thinking Skill (HOTS) bagi Guru-Guru Fisika di SMA Di Kota Depok - Tri Isti Hartini; Martin Martin (Jurnal Indonesia Mengabdi, 2019)
This service activity was motivated by the growing system of learning in educational institutions. Reality in the field, questions that are more discussed aspects of memory. Therefore, he felt that teachers, especially physics teachers, needed to be trained in making HOTS questions. In this service activity, the first session discussed the issue of HOTS in a discussion that included the understanding, steps of implementation, and its advantages. The second session was a deepening of the material followed by training on the questions raised about HOTS in teaching and learning activities. The method used in carrying out this service activity is the lecture method, question and answer, discussion, and direct practice. Based on observations during the community service activities, several positive results were obtained, which were expected to be: 1). The participants showed very high attention to the service material delivered by the service team. 2). The participants showed positive reactions to how to develop HOTS questions. 3). The active participants asked and revealed the problems they had experienced so far and they were happy to be able to make HOTS questions in the discussion. The results of this service activity add insight to physics teachers who are members of the Depok City Physics MGMP about making HOTS questions.